Did Protestantism promote prosperity via higher human capital? Replicating the Becker–Woessmann (2009) results. (6th August 2021) - Edwards, Jeremy
Summary: This paper shows that the Becker–Woessmann reformulation of the Weber thesis—Protestants were more prosperous in 19th‐century Prussia because they had higher human capital—is untenable. Regional variations in the Prussian institutional framework influenced economic outcomes, but Becker and Woessmann's econometric analysis takes no account of these variables, which suggests that their instrumental variable—distance to Wittenberg, a spatial variable—is invalid. When these regional effects are taken into account, 19th‐century Prussia provides no evidence that Protestantism increased prosperity by increasing human capital.